ATP/P2X7 receptor/NLRP3 pathway facilitates renal tubular epithelial-myofibroblast transdifferentiation and interstitial fibrosis in rats with unilateral ureteral obstruction - Tan, Hui; Li, Feiyan; Cui, Yanchao; Li, Ziwen; Yan, Shiqiang; Deng, Quanfeng (Frontiers in Pharmacology, 2025)
BackgroundP2X7 receptor (P2X7R) is reported involved in renal fibrosis and the activation of NOD-like receptor protein 3 (NLRP3) inflammasome. This study aimed to investigate the role of the P2X7R and NLRP3 in renal tubular epithelial-myofibroblast transdifferentiation (TEMT) and interstitial fibrosis using a rat unilateral ureteral obstruction (UUO) model.MethodsSprague‒Dawley rats were randomly divided into the following three groups: sham, UUO, and UUO + Brilliant Blue G (BBG). BBG (50 mg/kg/d)—an antagonist of the P2X7R—was injected intraperitoneally in UUO-treated rats. The adenosine 5′-triphosphate (ATP) concentration in kidney tissue was measured. Hematoxylin and eosin staining and Masson’s trichrome staining were used to evaluate the renal injury and the deposition of the extracellular matrix. Collagen-I, collagen-III, α-smooth muscle actin (α-SMA), P2X7R and NLRP3 expression levels were measured via immunohistochemical staining. Furthermore, the mRNA levels of α-SMA, P2X7R and NLRP3 were investigated via a reverse transcription-quantitative polymerase chain reaction.ResultsSignificant histopathological damage, which involved tubular dilatation, interstitial inflammation, and collagen accumulation, was observed in UUO rats and was notably alleviated via BBG administration. In the UUO group, ATP concentration increased considerably in kidney tissues; however, this concentration did not decrease following BBG treatment. Collagen-Ⅰ and -III expression levels were upregulated in UUO rats and attenuated through the administration of BBG. Furthermore, BBG administration ameliorated the accumulation of myofibroblast. P2X7R and NLRP3 protein and mRNA expressions increased notably in obstructed kidneys, whereas the protein and mRNA expression of NLRP3 appeared to reduce significantly in the BBG group. However, the mRNA level of P2X7R did not change in response to BBG treatment.ConclusionThe ATP/P2X7R/NLRP3 pathway is involved in renal TEMT and interstitial fibrosis. P2X7R antagonists attenuate renal interstitial fibrosis and may potentially be used as effective therapeutic agents.